Cinematic reflections: Maqāṣid al-Sharīʿa perspectives on sustainable film-induced tourism in Malaysia - Mazli, Muhammad Haniff Najmi; Md Sawari, Siti Salwa (Korint Yayincilik, 2024)
The objective of this research is to investigate the integration of Islamic principles into Film-Induced Tourism Destinations in Malaysia based on Maqāṣid Al-Sharīʿa. Content analysis serves as the primary method for data collection, incorporating Islamic attributes into the guidelines for Film-Induced Tourism Destinations using Maqāṣid Al-Sharīʿa. The analysis utilizes literature as a methodological tool. The identified guidelines are categorized into key attributes of Film-Induced Tourism Destinations, covering place branding, destination marketing, environmental sustainability, socio-cultural aspects, as well as infrastructure and technology development. The research's findings could enhance the film industry's comprehension of integrating Islamic guidelines into film-related tourism, fostering cultural sensitivity and respect. In terms of strategic development, the guidelines may aid the film industry in aligning strategically with Islamic principles, potentially expanding its appeal and reach.